1987
DOI: 10.1007/bf01127680
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal absorption of biotin and biocytin in the rat

Abstract: The uptake of biotin and biocytin was investigated in rat intestine using the everted sac technique. It has been shown that at biotin and biocytin concentrations less than 40 and 50 nM respectively, absorption proceeds by a saturable process, whereas at higher concentrations uptake by passive diffusion predominates. Fractionation of solubilized brush border preparations indicates that biotinidase is the only protein which binds biotin in this preparation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…On the other hand, the radioactivity in the intestine was not blocked by D-biotin pretreatment. It is reported that biotinidase, which is involved in the transport of biotin, exists in the intestine [36]. Thus, radioactivity accumulation in the intestine would reflect the behavior of 18 F-FBB itself, and not its binding to POS.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the radioactivity in the intestine was not blocked by D-biotin pretreatment. It is reported that biotinidase, which is involved in the transport of biotin, exists in the intestine [36]. Thus, radioactivity accumulation in the intestine would reflect the behavior of 18 F-FBB itself, and not its binding to POS.…”
Section: Discussionmentioning
confidence: 99%
“…Cohen & Thomas [11], using fully differentiated 3T3-L1 cells, further substantiated this hypothesis. It has been shown that at biotin and biocytin concentration of less than 50 nm absorption proceeds by a saturable process, whereas at higher concentrations uptake by passive diffusion predominates in the rat intestine [12]. Fractionation analysis of solubilized rat intestinal brush-border preparation indicated that biotinidase is the only protein which binds biotin in this preparation [12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that at biotin and biocytin concentration of less than 50 nm absorption proceeds by a saturable process, whereas at higher concentrations uptake by passive diffusion predominates in the rat intestine [12]. Fractionation analysis of solubilized rat intestinal brush-border preparation indicated that biotinidase is the only protein which binds biotin in this preparation [12]. Thoene et al [13] suggested that in humans normal biotin uptake could be the result of two systems, one with low Km (saturable) and the other with a high Km for biotin absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Under different osmotic pressures, several factors may simultaneously influence the absorption of VBs. Firstly, the uptake of most VBs was shown to be a specific carrier‐mediated transport system at low concentration combined with a simple diffusion at high concentration (Casirola, Ferrari, Gastaldi, Patrini, & Rindi, ; Dakshinamurti, Chauhan, & Ebrahim, ; Daniel, Wille, & Rehner, ; Feder, Daniel, & Rehner, ; Middleton, ; Merrill, Edmondson, & McCormick, ; Said, Hollander, & Duong, ; Stein & Diamond, ; Stein et al, ). Low concentration of sodium will lead to a fall in uptake (Casirola et al, ).…”
Section: Resultsmentioning
confidence: 99%